Implementasi Metode MOORA pada Sistem Prediksi Varietas Padi Berdasarkan Karakteristik Tanah - Eko Fuji Pangestu; Otong Saeful Bachri; Agyztia Premana (Fakultas Teknik Universitas Persada Indonesia YAI, 2026)
Rice crop productivity is influenced by the balance between the cultivated variety and soil characteristics. In Tanjung District, Brebes Regency, the selection of rice varieties is largely based on farmer experience, often without objectively considering soil conditions. This study aims to implement the Multi-Objective Optimization on the Basis of Ratio Analysis (MOORA) method to determine suitable rice varieties based on soil characteristics. The study utilizes five criteria soil pH, effective soil depth, soil moisture, drainage conditions, and soil texture and evaluates ten alternative rice varieties. The MOORA method involves constructing a decision matrix, normalization, weighting, calculating optimization values ​​(Yi), and ranking the alternatives. The results indicate that the Ciherang, IR64, Inpari 32 HDB, Inpari 34 Salin Agritan, and Inpari 35 Salin Agritan varieties achieved the highest optimization value (Yi) of 0.3441, making them the recommended varieties best suited to the analyzed soil characteristics. The application of the MOORA method provides objective and systematic rice variety recommendations, thereby supporting the decision-making process for variety selection based on soil conditions.